2016
DOI: 10.15280/jlm.2016.6.1.16
|View full text |Cite
|
Sign up to set email alerts
|

Health System Development and Performance in Korea and Japan: A Comparative Study of 2000-2013

Abstract: BackgroundThe Japanese and Korean healthcare systems are very similar and thus, they have the same problems and weaknesses. This study discusses the problems and proposes complementary solutions based on the results of a comparative analysis of conditions in the healthcare systems of the two countries.MethodsThis article presents a comparative analysis of the healthcare status of the two countries based on certain health criteria used worldwide, a literature review, and data from the Korean Ministry of Health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…In the present study, the clinical outcomes were consistent with those of a previously published national report in Japan [ 7 ]. Nakajima et al showed that 53.5% of all patients required MV and that most deaths occurred in the older adult group, which could be explained by the similarity in the healthcare insurance system and medical accessibility between the two countries [ 16 ]. Studies have shown that tetanus severity is associated with older adult patients, even for different healthcare insurance systems.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the clinical outcomes were consistent with those of a previously published national report in Japan [ 7 ]. Nakajima et al showed that 53.5% of all patients required MV and that most deaths occurred in the older adult group, which could be explained by the similarity in the healthcare insurance system and medical accessibility between the two countries [ 16 ]. Studies have shown that tetanus severity is associated with older adult patients, even for different healthcare insurance systems.…”
Section: Discussionmentioning
confidence: 99%
“…South Korea has experienced rapid decreases in both mortality and fertility, which have contributed to increasing the population age [19]; consequently, the proportion of children (aged 0–14 years) among the whole population is decreasing (Table 1). However, the incidences of pediatric traumatic injury in both datasets increased over time (Fig 2).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study indicated that Morimoto’s HPI was more useful when examining the association between health behaviors and the risk for MetS in Japanese samples compared with Breslow’s HPI [ 4 ]. Since there are many similarities in lifestyles between Korea and Japan, which are both Asian cultures, we used Morimoto’s HPI [ 29 ].…”
Section: Methodsmentioning
confidence: 99%